Longitudinal Analysis of P100 Wave Amplitude and Latency in Multiple Sclerosis: A 19-Year Retrospective VEP Study - Manuela Andreea Ciapă; Vlad Constantin Donica; Claudia Florida Costea; Camelia Margareta Bogdănici (Diagnostics)
Background: The diagnosis of multiple sclerosis (MS) relies on identifying neurological signs and symptoms, supported by evidence of central nervous system (CNS) dissemination of lesions across time and space. The visual pathway is commonly involved in MS, with a frequent involvement of optic neuritis (ON) episodes. Our study aims to assess the relationship between neuronal damage and optic nerve demyelination by analyzing the latency and amplitude of the p100 wave complex using visual evoked potentials (VEPs). Methods: We conducted a retrospective longitudinal study, analyzing VEP records of 15 patients with recurrent remissive MS at baseline, 5, 10, 15, and 19 years. Results: In 30 eyes we observed an increase in p100 wave latency at 5-years by 14.35 ± 4.47 ms (p = 0.003), at 10-years by 19.26 ± 4.87 ms (p < 0.0005) and a decrease in amplitude by 2.29 ± 0.52 mV (p < 0.0005) when comparing to baseline values. At 15-years, 24 eyes presented an increase in latency of 31.39 ± 7.8 ms (p = 0.001) and a decrease in amplitude of 2.51 ± 0.6 mV (p < 0.0005) compared to baseline, while at 19-years, 10 eyes presented an increase in p100 wave latency of 53.45 ± 18.42 ms (p = 0.018) and a further decrease in amplitude of 4.06 ± 1.32 mV (p = 0.014). We found correlations between the p100 wave latency and amplitude at baseline, 15-year, and 19-year follow-ups, increasing from a low negative (r = −0.43) to medium negative (r = −0.502) and finally high negative (r = −0.906) correlation. Conclusions: VEPs have long been acknowledged for their ability to detect both clinical and subclinical lesions in MS cases. Our study offers new insight into the relationship between demyelination and axonal degeneration observed when analyzing the latency and amplitude of the p100 wave complex during VEP in a longitudinal analysis.